The effect of essential oil concentrations on particle size of kencur (Kaempferia galanga L.) nanoemulsions with maltodextrin and tween 80 as emulgators - Amri Setyawati; Febi Fajarwati Indah; Yuniar Kusuma Ardani (Jurnal Pijar Mipa, 2022)
Kencur (Kaempferia galanga L.) essential oil nanoemulsion was proposed to replace baby powder which has been banned in several countries. This study aimed to determine the effect of various kencur essential oil concentrations on particle size and to measure their stability during storage. This research was initiated by examining essential oil quality and followed by the formulation of nanoemulsion with maltodextrin and tween 80. PSA characterized it, and stability was observed for six weeks. The results showed that the essential oil of kencur was of good quality with a clear yellow color oil, a distinctive odor of kencur, 0.933 g/mL of density, and a 1.480 refractive index value. This value is considered standard in Indonesia's National standards (SNI) of essential oil. The L1, L2, L3, and L4 nanoemulsion formulas have particle sizes: 20.4 nm, 20.3 nm, 21.7 nm, and 26.2 nm, respectively. L1 (0.475) is chosen as the best formula based on the PI value. The formulas showed good stability and homogeneity for six weeks of storage. Its pH is also persistent at room temperature (30 °C) or in refrigerator storage (7 °C).